PENGARUH VIRAL MARKETING DAN TURBO MARKETING TERHADAP KEPUTUSAN PEMBELIAN SKINCARE SCARLETT PADA TOKO JELITA COSMETIC BIMA - Suffiah; Ismunandar (JURNAL ILMIAH RESEARCH STUDENT, 2023)
. The purpose of this study was to determine how the influence of viral marketing and turbo martketing on purchasing decisions. Method method used in this research is the Associative method. With instruments using a Likert scale questionnaire. This research location was conducted at the Jelita Cosmetic Bima Store Jl. Sulawesi No.21 Bima City. The population used in this study are all consumers who have bought scarlett skincare at the Jelita Cosmetic Bima store which is not known with a research sample of consumers who have ever bought and consumers who are 17 years old. consumers who have bought and consumers who are 17 years of age and over. The result in this study is Viral Marketing has a significant effect on purchasing decisions. significant on purchasing decisions. This This means that Viral Marketing at Jelita Cosmetic Bima Shop influences the Scarlett Skincare purchasing decision at the Jelita Cosmetic Bima Store. Turbo Marketing has a significant effect on purchase decision. This means that Turbo Marketing is not significant on purchasing decisions for Scarlett Skincare at Jelita Cosmetic Bima Store. Viral Marketing and Turbo Marketing simultaneously have a significant effect on purchasing decisions for Scarlett Skincare at Jelita Cosmetic Bima Store.